2019
DOI: 10.32947/ajps.v19i1.547
|View full text |Cite
|
Sign up to set email alerts
|

The Cytotoxic Effect of Metformin on RD Cell Line.

Abstract: Background: Cancer is a pathogenesis that happens when modification in collections of normally occurring cells inside the human body occurs leading to non-controlled growth causing a lump called the tumor; this applies to all types of cancers except leukemia (cancer of  the blood). Doxorubicin (DOX) is one of the highly effective anti-neoplastic drugs of the anthracycline's family used to treat many pediatric and adult cancers, e.g. solid tumors, lymphomas, leukemia and breast cancer. Doxorubicin is know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“… 26 (Paiva-Oliveira DI et al2018) [48] . Osteosarcoma Spheres of MNNG/HOS and MG-63 osteosarcoma cell lines Cytotoxicity, cell viability DOX (0.25 Um), Met (5 mM), 48 h Activation of AMPKα signaling pathway 27 (Mohammd AW et al2019) [49] . Breast cancer MCF-7 cell lines Cytotoxicity, proliferation arrest, apoptosis DOX5 uM and Met 10 mM 72 h Met-exhibits a cytoprotective effect, reducing both basal and postprandial glucose levels through the attenuation of ROS production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 (Paiva-Oliveira DI et al2018) [48] . Osteosarcoma Spheres of MNNG/HOS and MG-63 osteosarcoma cell lines Cytotoxicity, cell viability DOX (0.25 Um), Met (5 mM), 48 h Activation of AMPKα signaling pathway 27 (Mohammd AW et al2019) [49] . Breast cancer MCF-7 cell lines Cytotoxicity, proliferation arrest, apoptosis DOX5 uM and Met 10 mM 72 h Met-exhibits a cytoprotective effect, reducing both basal and postprandial glucose levels through the attenuation of ROS production.…”
Section: Resultsmentioning
confidence: 99%
“…Correspondingly, Kabel et al ( Table 2 ) reported that metformin reduces SphK1 activity and shifts the sphingolipid rheostat towards reduced S1P production [36] . Additionally, a study reported that metformin can exert a cytoprotective effect by decreasing the production of ROS [49] . Doxorubicin can initiate ROS production by binding to cardiolipin and triggering electron leakage by disrupting its function; ROS itself can prompt cell cycle arrest and cell death [9] .…”
Section: Discussionmentioning
confidence: 99%
“…The methodology used to investigate the anticancer activity of (P1-P6) on viability of Lung Cancer Cell Line (A549) by MTT assay (25) was carried out at the College of Pharmacy/ Mustansiriyah University, Iraq. _____________________________________________________________________________________________________________ ________________________________________________ Egypt.…”
Section: Cytotoxic Assaymentioning
confidence: 99%